The Effect and Possible Mechanism of Intradiscal Injection of Simvastatin in the Treatment of Discogenic Pain in Rats - Huang, Xiaodong; Zheng, Changkun; Wang, Weiheng; Ye, Xiaojian; Lin, Chia-Ying; Wu, Zenghui (Frontiers in Neuroscience, 2021)
To study the effect of intradiscal injection of simvastatin on discogenic pain in rats and its possible mechanism. 30 adult female rats were used in this experiment. Twenty rats were randomly divided into sham operation group (Control group), intervertebral disc degeneration group (DDD group), intervertebral disc degeneration + hydrogel group (DDD + GEL group), intervertebral disc degeneration + simvastatin group (DDD + SIM group). The mechanical pain threshold and cold sensation in rats were measured. The contents of NF-kappa B1, RelA, GAP43, SP, CGRP, TRPM 8, IL-1β and TNF-α in the intervertebral disc, the corresponding contents of dorsal root ganglion (DRG) and plantar skin GAP43 and TRPM 8 were quantitatively detected by PCR. The corresponding intervertebral discs were stained to detect their degeneration. There was no significant difference in the mechanical pain threshold between the groups at each time point. From the first day to the 8th week after surgery, the cold-sensing response of the DDD group was significantly higher than that of the Control group (p < 0.05). At 7 and 8 weeks postoperatively, the cold-sensing response of the DDD+SIM group was significantly lower than that of the DDD+GEL group (p < 0.05). The levels of NF-κB1, RelA, GAP43, SP, CGRP, TRPM8, IL-1β and TNF-α in the intervertebral disc of DDD+SIM group were significantly lower than those in DDD group (p < 0.05); The content of GAP43 and TRPM8 in rat plantar skin decreased significantly and TRPM8 in DRG decreased significantly (p < 0.05).